Chapter 9 – Rules for the future: forecasts and hindcasts - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED • How do discuss and agree on fishery management plans for the future? • Can we develop harvest rules in small-scale fisheries, without models? • How can we express the probable costs of fishing too much or too little? Forecasts and harves rules - parametric quotas Adaptive harvest rules - non-parametric